Pengaruh Komitmen Organisasi Dan Penerapan Kode Etik Aparat Pengawasan Intern Pemerintah terhadap Kinerja Auditor Pemerintah (Studi Kasus pada Badan Pengawasan Keuangan dan Pembangunan Perwakilan Daerah Istimewa Yogyakarta) - Ayem, Sri (AKMENIKA, 2018)
The purpose of the study is todetermine the influence of organization commitment, integrity, objectivity, confidentiality, and competence to the internal auditor performance BPKP Perwakilan DIY partially and simultaneously. The data used in this research is primary data obtained from the distribution of questionnaires to the respondents. The population in this study are functional officials of auditors in BPKP Perwakilan DIY, with a sampling technique using a purposive sampling turn sout to48 auditors.The analysis method used in this research is multiple linear regression analysis. The results show that organization commitment ,integrity, objectivity,confidentiality, and competence have significant influence to the auditor performance simultaneously. But, only competence variable affects the auditor performance partially.